Whiting out Algeria: On the Limits of Assia Djebar's Le Blanc de l'Algérie as Post-Traumatic Liturgy. Issue 2 (August 2018) - Talbayev, Edwige Tamalet
Abstract : This essay reflects on Assia Djebar's mode of memorialisation of the symbolic and aesthetic aftermath of the Algerian Black Decade – and of the forms of collective trauma that it instigated. It probes Djebar's 'writing after' aesthetics in Le Blanc de l'Algérie (1995): a counter-political, afterwardly literary idiom dedicated to deflating ready-made forms of memorialisation. It examines the way in which Djebar avails herself of a post-literary, utopian language – her 'poetics of white' – to adequately attend to the multiple voices of Algeria. By recovering those vanishing testimonies in their singularity, Djebar's retrospective vision of the legacy of violence recasts the present as aftermath. Providing a deep-reaching reflection on the appropriate liturgy befitting her future-oriented memorial project, one tethered to 'a nation seeking its own ceremonial', Djebar illuminates the purview of the post-literary to bear witness to the origin of the violence, 'the why of yesterday's funerals, those of the Algerian utopia', with the aim of excavating new models of living together. However, Djebar's text falls prey to hermeneutic limits that mark out the narrator's disintegration and her inability to truly lend a voice to those bereft of their own. The example of Djebar's 'poetics of white' thus offers a reflection on the effects of narrative dissolution – here the dissolution of the narrative voice – in memorial mediations of the afterwardly. Can a countertextual literary practice, one aiming at speaking against coercive political forms, move beyond the aporetically singular? Can it ever fulfil a collective project, or is it doomed to dissolution and expatriation?